Expanding game, expanding opportunity: the effect of athlete migration on Czech ice hockey from 1993 to 2018 - Crossan, W. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
This paper analyzes the last 25 years of sport migration in men`s elite and youth ice hockey in the Czech Republic. In light of the primary cultural position of ice hockey in the nation, migration to play the game shapes cultural identity. The migration of Czech players who control the rise and fall of this ice hockey identity, is seen to be influenced by European Union ascension, as well as decisions and policies of the prestigious, expanding and increasingly commercialized NHL and KHL. Flows and donors into the top Czech leagues are also explored from the separation of Czech and Slovakia in 1993 through the 2017-2018 season. The study relies on secondary quantitative data from a multitude of sources in order to more fully understand the complex influencers and ramifications of sport migration on a primary sport in a periphery country for an expanding game.